1996
DOI: 10.2307/3870409
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Calcium Signaling Involved in Cell Volume Control in the Fucus Rhizoid

Abstract: Subprotoplasts prepared from different regions of rhizoid and thallus cells of Fucus zygotes displayed mechanosensitive plasma membrane channels in cell-attached patch-clamp experiments by using laser microsurgery. In excised patches, this channel was found to be voltage gated, carrying K+ outward and Ca2+ inward, with a relative permeability of Ca2+/K+ of 0.35 to 0.5, and an increased open probability at membrane potentials more positive than -80 mV. No significant difference was found in the density of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 0 publications
2
75
1
Order By: Relevance
“…Silanisation of the pipettes enhanced seal formation. Treating pipette tips with 0-001 % (w/v) poly-L-lysine has been reported to enhance seal formation to the plasma membrane of Fucus (Taylor et al, 1996) though this treatment did not enhance seal formation in the present study. To reduce pipette capacitance, electrodes were coated with a 50 % (w/w) mixture of mineral oil (Sigma, Poole, UK) and Parafilm® (American National Can., Chicago, IL).…”
Section: Electrophysiologycontrasting
confidence: 54%
See 2 more Smart Citations
“…Silanisation of the pipettes enhanced seal formation. Treating pipette tips with 0-001 % (w/v) poly-L-lysine has been reported to enhance seal formation to the plasma membrane of Fucus (Taylor et al, 1996) though this treatment did not enhance seal formation in the present study. To reduce pipette capacitance, electrodes were coated with a 50 % (w/w) mixture of mineral oil (Sigma, Poole, UK) and Parafilm® (American National Can., Chicago, IL).…”
Section: Electrophysiologycontrasting
confidence: 54%
“…Laser ablation of the cell wall to expose the plasma membrane has been used as a tool for investigations of algal cells (Taylor & Brownlee, 1992;DeBoer et al, 1994;Taylor et al, 1996) and higher plant cells (Kurkdjian et al, 1993;Henricksen et al, 1995); though only two studies have then successfully applied the patch-clamp technique to characterize ion channels in the exposed plasma membrane (Henricksen et al, 1995;Taylor et al, 1996). In the present study, we have shown that it is feasible to use the laser ablation technique to produce plasma membrane-bound blebs at defined locations along the hyphae of Aspergillus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the ROS/ hyperpolarization-activated Ca 21 channel thought to support the gradient in root hairs (Foreman et al, 2003) and such a mechanical response remains to be defined. It is probable that more than one Ca 21 -permeable channel exists at the tips of root hairs, similar to the tip-growing rhizoids of Fucus, which contain two Ca 21 -permeable channels, one with and one without mechanosensitivity (Taylor et al, 1996). Integration of the activity of these channels may well lie at the heart of the system that must precisely balance the promotion and restriction of turgor-driven expansion to permit root hair elongation without runaway expansion and the associated catastrophic failure of the apical wall.…”
Section: Discussionmentioning
confidence: 99%
“…This initiation site is an important model for other plant cells. Taylor et al (1996) used laser microsurgery and patchclamping on the Fucus rhizoid tip plasma membrane. Voltage-regulated and mechano-sensitive channels that carry Ca 2+ were detected in the plasma membrane of the tip.…”
Section: The Calcium Wavementioning
confidence: 99%